Integrative multi-omics identification and functional validation of potential targets linking metabolism–immune–colorectal cancer causal pathway - Zheng, Zequn; Xu, Xiaoling (Frontiers in Immunology, 2025)
IntroductionColorectal cancer (CRC) remains a major global health burden, highlighting the need for novel molecular targets for therapy and prognosis. This study integrates multi-omics data with functional assays to explore metabolite-mediated mechanisms in CRC risk.MethodsWe performed genetic causal inference and colocalization analyses using genome-wide association data to assess causality between 233 metabolites and CRC. A total of 731 immune traits were investigated as potential mediators. Metabolite-associated CpG sites were identified via epigenome-wide association studies (EWAS), and their methylation QTLs (mQTLs) were linked to target genes through interaction eQTL analysis via FUMAGWAS. Expression, prognosis, immune infiltration, and regulatory associations of target genes were analyzed using TCGA datasets. Functional assays were conducted in NCM460 and CRC cell lines (HCT116, SW480, CACO2). CRC xenograft mice were used to monitor tumor growth in vivo.ResultsA higher omega-3 fatty acid ratio (FAw3byFA, OR = 1.22, P = 2.51×10-7) was associated with increased CRC risk, with partial mediation (10%) via Effector Memory CD4+ T cells. Colocalization (PP.H4 ≈ 0.97) suggested shared genetic loci. Genetically predicted omega-3-associated CpG sites, cg05181941, cg06817802, and cg22456785, were linked to CRC risk. These sites-derived 428 mQTLs interact with eQTL genes, highlighting SLC6A19 as a potential target, expressed in CD4+ T cells , colon tissue and CRC epithelial cells. SLC6A19 was downregulated in TCGA-COAD, -READ, and -COADREAD and confirmed by immunoblotting, correlating with poor survival and CD4+ T cell infiltration. CCK-8, wound healing, and Transwell assays showed that SLC6A19 overexpression suppressed CRC cell proliferation, migration, and invasion. In vivo, SLC6A19 overexpression significantly reduced CRC xenograft tumor growth.ConclusionsOmega-3-related methylation-intersecting SLC6A19 potentially mediates omega-3-CD4+ T cells-driven CRC risk, suggesting a candidate inhibitory target.